Windows 11 For Dummies - Rathbone, Andy (For Dummies, 2022)
Need Windows help? Find the latest tips and tricks in this perennial favorite on Windows Windows 11 promises to be the fastest, most secure, and most flexible version of the Microsoft operating system yet. With a promise like that, of course you want to start using it, as quickly as possible! Windows 11 For Dummies gives you that speed, security, and flexibility by getting you up to date with the latest in Windows. Windows expert and bestselling author Andy Rathbone gives you a helping hand by showing you how to get around the newly updated Windows 11 interface, how to use the new Windows tools like Teams and widgets, and how to use Android apps. Your tour of Windows 11 starts with the Start menu and ends with how to troubleshoot when things go wrong. In between you find out how to find files on your hard drive, connect with friends and colleagues on Microsoft Teams, transfer photos from your phone to your hard drive, or switch between your desktop and laptop. Additional topics include: Navigating the Start menu Finding where your files are hiding Adding separate user accounts to keep your kids out of your business Connecting to a WiFi network Customizing your widgets Switching to a laptop or tablet You know what you want to get done. Keep Windows 11 For Dummies by your desktop, laptop, and tablet, and you can open it at any time to find out how to get your Windows computer to do what you need.